News on the move: Towards a typology of Journalists in Exile - O'Loughlin,Conor (2016)
Over the last eleven years, 706 journalists around the world have been forced to flee their homelands as a direct consequence of their work. The aim of this study is to provide insight into how the experience of going into exile has affected the motivations and professional standards of these journalists. The study consisted of in-depth interviews with journalists from five countries who have previously fled their homelands. The study shows that adherence to the truth, a basic tenet of journalism in a liberal democracy, is a cornerstone of professional practice for these journalists. Journalists can be seen to have a bi-dimensional relationship with the truth, considering it an end in itself but also recognising its utility value to help further their democratising goals. Journalists' motivations were also found to be strong towards helping create a better country for their compatriots. Motivations were found to be symbolic or functional. A typology of journalists in exile is proposed. The results are discussed in the context of relevant literature on the roles of journalists in and out of democracies.